Acute amino acids supplementation enhances pituitary responsiveness in athletes - DiLuigi, L.; Guidetti, L.; Pigozzi, F.; Baldari, C.; Casini, A.; Nordio, M.; Romanelli, F. (Medicine & Science in Sports & Exercise, 1999)
Purpose: The purpose of this study was to determine the effect of a mixture of amino acids on pituitary responsiveness to a stimulation test (GnRH + CRH) in athletes. Methods: In a double blinded counterbalanced experimental protocol, 10 moderately trained male athletes performed the pituitary stimulation test 60 min after a single oral administration of a placebo (Pl-AS) or an amino acid mixture solution (AS) (L-arginine hydrocloride 100 mg·kg-1 + L-ornithine hydrocloride 80 mg·kg-1 + L-branched chain amino acids 140 mg·kg-1: 50% L-leucine, 25% L-isoleucine, 25% L-valine) on two different occasions. Plasma ACTH, LH, FSH, GH, and cortisol were evaluated before (-60, -30, 0 min) and after (+15, +30, +45, +60, +90 min) the stimulation test. Results: The ACTH, LH and FSH response to CRH + GnRH was significantly higher in AS group both as absolute values and area under curve (AUC) values than in Pl-AS group. Pre-test and post-test cortisol AUC levels were significantly higher in Pl-AS group although a higher percent increase in post-test cortisol was found in AS group. The total GH-AUC was higher in AS group and, as expected, the absolute GH concentrations at different time points were not influenced by CRH + GnRH administration. Conclusion: The amino acid mixture used enhanced the ACTH, LH, and FSH response to CRH + GnRH.